Effect of Pulse Duration and Direction on Plasticity Induced by 5 Hz Repetitive Transcranial Magnetic Stimulation in Correlation With Neuronal Depolarization - Halawa, Islam; Reichert, Katharina; Aberra, Aman S.; Sommer, Martin; Peterchev, Angel V.; Paulus, Walter (Frontiers in Neuroscience, 2021)
Introduction: High frequency repetitive transcranial magnetic stimulation applied to the motor cortex causes an increase in the amplitude of motor evoked potentials (MEP) that persists after stimulation. Here, we focus on the aftereffects generated by high frequency controllable pulse TMS (cTMS) with different directions, intensities and pulse durations. Objectives: To investigate the influence of pulse duration, direction, and amplitude in correlation to induced depolarization on the excitatory plastic aftereffects of 5 Hz rTMS using bidirectional cTMS pulses. Methods: We stimulated the hand motor cortex with 5 Hz rTMS applying 1,200 bidirectional pulses with the main component durations of 80, 100 and 120 microseconds using a controllable pulse stimulator TMS (cTMS). Fourteen healthy subjects were investigated in nine sessions with 80% resting motor threshold (RMT) for posterior–anterior (PA) and 80% and 90% RMT anterior-posterior (AP) induced current direction. We used a model approximating neuronal membranes as a linear first order low-pass filter to estimate the strength–duration time constant and to simulate the membrane polarization produced by each waveform. Results: PA and AP 5 Hz rTMS at 80% RMT produced no significant excitation. Only the 100 and 120 µs pulses with 90% RMT AP stimulation led to significant excitation. We found a positive correlation between the plastic outcome of each session and the simulated peak neural membrane depolarization for time constants greater than 100 microseconds. This correlation was strongest for neural elements that are depolarized by the main phase of the AP pulse, suggesting the effects were dependent on pulse direction. Conclusions: Among the tested conditions, only 5 Hz rTMS with higher intensity and wider pulses was successful in producing excitatory aftereffects. This correlated with the greater depolarization of neural elements with time constants slower than the directly activated neural elements responsible for producing the motor output (e.g.: somatic or dendritic membrane). Significance: Higher intensities and wider pulses seem to be more efficient in inducing excitation. This could yield better results in future clinical studies performed with wider pulses